Experimental investigation on the flow mixing and core length of a supersonic multiple jet configuration using cross-wire as vortex generators - Faheem, Mohammed; Khan, Sher Afghan; Alam, Mohammad Mukhtar; Arputharaj, Beena Stanislaus; Hussain, Fayaz; Al-Mdallal, Qasem M. (Elsevier Ltd, 2025)
Many Engineering applications utilize multi-jet systems, such as those found in aircraft propulsion units and spacecraft. A complex aerodynamic flow field occurs when multiple jets are close to each other. This study experimentally examines the supersonic jets’ mean flow field and mixing characteristics from one, two, and three different converging-diverging nozzles placed in close vicinity. The cross-wire is used as a passive control technique to investigate the impact of the control on the flow field and the core length. The nozzle is designed for a Mach number of M = 1.5, with an inter-nozzle positioning equal to twice the nozzle exit diameter. The typical contact procedure and the growth of the triple jet are discussed using cross-sectional contour patterns and transverse pressure profiles. The effect of leading parallel jets on local flow field features, comprising shock wave structure, supersonic core, and jet spread, is observed by measuring pressure beside the jet axes. Similarly, the flow spread rate declines when the quantity of jet flow increases; this is mainly due to a decrease in the attainability. Consequently, the jet decays more slowly, and the core length decreases. Schlieren’s pictures of triple, twin, and single jets reveal that the core of the supersonic jet varies in triple and twin jets compared to single jets.